Islamic Educational Values in The Quran (A Study on The Story of Prophet Sulaiman) - Nahar, Syamsu; Budianti, Yusnaili; Pasaribu, Harsono (Tarbiyah Wa Ta'lim: Jurnal Penelitian Pendidikan dan Pembelajaran, 2024)
-